Establishing a clinical service for the treatment of osteoid osteoma using magnetic resonance-guided focused ultrasound: overview and guidelines. Issue 1 (December 2016) - Temple, Michael; Waspe, Adam; Amaral, Joao; Napoli, Alessandro; LeBlang, Suzanne; Ghanouni, Pejman; Bucknor, Matthew; Campbell, Fiona; Drake, James
Abstract Recent studies have demonstrated the effectiveness of magnetic resonance-guided focused ultrasound (MRgFUS) in the treatment of osteoid osteoma (OO), a painful, benign bone tumor. As MRgFUS is a noninvasive and radiation-free treatment, it stands to replace the current standard of care, percutaneous radiofrequency, or laser thermal ablation. Within an institution, creation of a clinical OO MRgFUS treatment program would not only provide cutting edge medical treatment at the current time but would also establish the foundation for an MRgFUS clinical service to introduce treatments currently under development into clinical practice in the future. The purpose of this document is to provide information to facilitate creation of a clinical service for MRgFUS treatment of OO by providing (1) recommendations for the multi-disciplinary management of patients and (2) guidelines regarding current best practices for MRgFUS treatment. This paper will discuss establishment of a multi-disciplinary clinic, patient accrual, inclusion/exclusion criteria, diagnosis, preoperative imaging, patient preparation, anesthesia, treatment planning, targeting and treatment execution, complication avoidance, and patient follow-up to assure safety and effectiveness.